High and low take-off external prolapse phenotypes can be characterised preoperatively on defaecation proctography - Cooper, EA; Singh, S; Yates, C; Hodgkinson, J; Cunningham, C; Lindsey, I (Springer, 2025)
Background: External rectal prolapse is poorly understood, with controversy surrounding the ideal surgical approach. Anecdotal mentions of high and low take-off in the literature hint at different pathological phenotypes of prolapse. However there has been no effort to define and characterise these terms, or to discuss how take-off might relate to the underlying pathophysiology of prolapse. We aimed to determine if defaecation proctography (DPG) could reliably characterise high and low take-off prolapse. Methods: The study was a retrospective analysis of prospectively collected data. A total of 88 patients with external rectal prolapse were investigated with a defaecating proctogram as part of their routine evaluation between January 2004 and December 2017. Prolapse take-off was determined by the level of origin on proctography. The rectosigmoid junction position at rest and caudal mobility during straining were also determined, relative to sacrococcygeal bony segmental level. Results: Take-off was characterised in all 88 patients (median age 64 years old, 92% female), of which 53 (60%) had high take-off and 35 (40%) low take-off prolapse. There was significantly greater rectosigmoid junction caudal mobility (median descent 9 vs 5 cm, p = 0.001, respectively) and a trend to significantly lower resting rectosigmoid position (median sacral level S4 vs S3, p = 0.08, respectively) in the high take-off group compared to low take-off. Conclusion: In this first formalised description and definition of take-off in the literature, we have shown that defaecating proctogram can satisfactorily identify, discriminate between and characterise two distinct external prolapse phenotypes. We propose two distinct causal pathways to external rectal prolapse, connective tissue failure and levator ani factors. Take-off should be a consideration as a prognostic in clinical practice and research trials.